Pengaruh Gaya Kepemimpinan Transaksional dan Kompensasi Terhadap Kinerja Karyawan PT. Era Elektra Corpora Indonesia - Fahmi, Ardian Binuril; Puspasari, Aprilia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Transactional Leadership Style is one of the key factors influencing employee performance. Another factor affecting employee performance is compensation. As a company engaged in the technology sector, particularly in the crucial field of weather radar, PT. Era Elektra Corpora Indonesia must optimize employee productivity. This study aims to analyze the influence of Transactional Leadership Style and Compensation on employee performance at PT. Era Elektra Corpora Indonesia. The research method used is quantitative with a saturated sampling technique, involving the entire population of 35 employees as respondents. Data were collected through workplace observation and structured questionnaires, then analyzed using Statistical Product and Service Solution (SPSS) version 25. Results indicate that, partially, Transactional Leadership Style (X1) has a positive and significant effect on Employee Performance (Y), with a t-count of 4.725 t-table of 2.03, a significance value of 0.000 0.05, and an R Square of 51.1%. Compensation (X2) also shows a positive and significant effect, with a t-count of 3.167 t-table of 2.03, significance value of 0.003 0.05, and an R Square of 36.9%. Simultaneously, both variables significantly affect performance, with an F-count of 27.018 3.29, significance 0.000 0.05, and a contribution of 60.5%, making them strategic factors in improving performance.